Impacts of artificial Caragana intermedia stand on soil texture evolution in desert steppe - Song Naiping; Wu Xudong; Pan Jun; Qu Wenjie; Zhou Juan; An Chaoping (浙江大学学报. 农业与生命科学版)
Planting Caragana has achieved remarkable success in the recovery of desertification land in desert steppe because of its excellent biological characteristics, such as tolerance of sand burying, drought-resistance, and so on. Thus, its sustainability of ecological restoration becomes one of the key topics of concern. Restoration of soil habitat is the foundation for ecosystem being fully restored, and soil texture is the core indicator to evaluate soil properties. In this study, soil texture evolution process and effects after planting C. intermedia stand were investigated to understand its role in desert steppe ecosystem.Series of different stand ages (10 a, 17 a, 27 a) and space sequences (from the inside via the edge to the outside of shrubs) were designed to analyze the spatiotemporal rules of soil particle composition, increment in silt and clay, volume fractal dimension of soil particles, as well as the contents of soil organic carbon (SOC) and soil total nitrogen (STN).The results showed that: 1) The percentages of fine sand (ranging from 0.05 mm to 0.1 mm) were higher than those of silt and clay, coarse sand and gravel sand in the soil particle composition. With the increase of C. intermedia stand ages, soil texture was improved gradually according with vertical orientation of soil depth from top to bottom and horizontal direction from the inside to the outside of shrubs. The volume fractal dimension of soil particles inside shrubs increased by 0.189±0.401 on average compared to the outside. 2) Spatial heterogeneity of SOC and STN in the surface soil layer changed significantly with the increase of C. intermedia stand ages. SOC and STN inside shrubs increased by (0.087±0.100)% and (0.008±0.010)% respectively in comparison to those outside shrubs, which indicated the fertility island effect by C. intermedia. The contents of SOC and STN were significantly and positively correlated with the content of silt and clay (P< 0.01). 3) Caragana intermedia plantation exerted a distinct co-succession influence on the content of silt and clay and the resource of carbon and nitrogen in desert steppe.In conclusion, soil texture and soil fertility states are significantly improved after the construction of Caragana plantation. However, soil texture is improved more slowly when plantation aged.